Relationship between empathy and personality traits in students of a Public Sector Medical University - Naeem Liaqat, Maria Ata, Nida -e- Haider, Naeem Liaqat, Maria Ata, Nida -e- Haider (Journal of Rawalpindi Medical College, 2022)
Introduction: Empathy among medical students and doctors, is rather unexplored part of medical flora and fauna which may vary with each personality. Objective: to determine the correlation between empathy and personality traits of final year medical students. Materials and Methods: This cross-sectional study was conducted at Rawalpindi Medical University, Pakistan. A total of 144 medical students were included in the study. For personality traits assessment and empathy assessment, Big Five Inventory and Interpersonal Reactivity Index were used. All the data was analyzed using SPSS version 20. Results: The mean score for empathy scale was found to be 61.25 ± 10.0. Females were more empathetic than males in all subscales but pointedly so in empathetic concern scale. Overall empathy scale was strongly correlated with Agreeableness and Neuroticism (P<0.001). Perspective taking scale was positively related with Agreeableness and openness, Empathy concern scale was positively related with Agreeableness, and Personal Distress was positively related with Conscientiousness and Neuroticism. The demographic factors of age and gender explained only 1.7%, 6.8%, 2.4% and 2.0% of the variance in the four scales of empathy. After adjustment for age and gender, perspective taking was positively associated with Agreeableness and Openness and Personal distress was associated with Agreeableness, Neuroticism and Openness. Conclusion: We conclude that personality traits have a substantial correlation with empathy and its subscales. So we need to evaluate the personality of a medical student and tailor a set of rules for each individual consistent with their persona to develop empathy in them. Keywords: Big Five; Personality; Empathy; Medical students; Pakistan